A taxonomic study of Chinese Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) (II) - Qin, Dao-Zheng; Liu, Yang; Zhang, Ya-Lin (Zootaxa, 2011)
A new empoascine genus, Membranacea Qin & Zhang, gen. n., with three new species (M. spinata Qin & Zhang, sp. n., M. unijugata Qin & Zhang, sp. n. and M. plana Qin & Zhang, sp. n.), from China are described. In addition, the genus Bhatasca Dworakowska, 1995 is newly recorded from the Chinese mainland and a new species, B. rectangulata Qin & Zhang, sp. n., is described. The genus Ghauriana Thapa, 1985 is reported for the first time from China and a new species, G. sinensis Qin & Zhang sp. n. is added to the Chinese typhlocybine fauna. Keys to all species in each genus are given. Habitus photos and illustrations of male genitalia of these new species are also provided.